The Recovery of "Criminal" Assets in New Zealand, Ireland and England: Fighting Organised and Serious Crime in the Civil Realm - Campbell, Liz (Victoria University of Wellington Law Review, 2010)
This article considers the enactment of the Criminal Proceeds (Recovery) Act 2009 in New Zealand, and compares it with the established processes of civil asset recovery in Ireland, England and Wales. Salient differences between the models are examined, including the more expansive definitions in Ireland. The article posits that the recovery process in these three jurisdictions in fact is a criminal one which merits the adoption of due process rights, given the promotion of the aims of punishment, the centrality of the targeted individual’s culpability, and the powers of the agencies involved. However, the case law in Ireland and England has concluded that the process is civil: perhaps the best that can be expected is the adoption of a "middle ground" approach, which encompasses protective rights while still operating in the civil sphere.